Análisis sociolingüístico de las jergas de los jóvenes del grupo Ángeles de Usme con respecto a su construcción social (2022)
Youth jargons are an expression and way of life of cultures, these jargons allow the representation and configuration to the identity groups. The proposal to investigate the jargon young’s people arises from the desire to understand social phenomena such as stigmas, judgments, misunderstandings, among others, which are attributed to the use of language. In this way, the social processes that are carried out to construct the youths jargons of Usme are investigated, as well as to determine to what extent jargons influence the way to the interaction of a group with society and how identity is created from them.